The Cambridge handbook of Japanese linguistics - Hasegawa, Yoko (Cambridge handbooks in language and linguistics, 2018)
"The Cambridge Handbook of Japanese Linguistics The linguistic study of Japanese, with its rich syntactic and phonological structure, complex writing system, and diverse sociohistorical context, is a rapidly growing research area. It consists of five thematic parts including sound system and lexicon, grammatical foundation and constructions, and pragmatics/sociolinguistics topics, with chapters that survey critical discussions arising in Japanese linguistics-- will be welcomed by general linguists, and students and scholars working in linguistic typology, Japanese language, Japanese linguistics and Asian Studies"-- Provided by publisher